(untitled) (Faridpur Medical College Journal, 2013)
Advanced abdominal pregnancy (AAP) with a viable full-term fetus is a rarity that a few obstetricians encounter during their professional carrier. Usually it has a dramatic and catastrophic consequence both for the fetus & the mother; rather subsequent delivery of a viable full term fetus is exceptional. It is difficult to diagnose preoperatively. Though relatively rare, we received an AAP at term with live fetus in Faridpur Medical College & hospital. Illiteracy, poverty and lack of antenatal care had resulted in her late presentation. After laparotomy the diagnosis was confirmed, a healthy male baby was delivered. DOI: http://dx.doi.org/10.3329/fmcj.v8i1.16898 Faridpur Med. Coll. J. 2013;8(1): 40-43